The in vitro influence of external electrostatic field on the lipid-protein interactions in membranes of rat erythrocytes. Issue 4 (6th July 2015) - Sahakyan, G.V.; Artsruni, G.G.; Poghosyan, G.A.
Abstract : Purpose: – The purpose of this paper is to investigate the in vitro influence of 200 kV/m electrostatic fields (ESF) on the microviscosity, viscosity and polarity of rat erythrocyte membranes for revealing the possible changes in lipid-protein interactions due to the field influence. Design/methodology/approach: – The investigation of the parameters of erythrocyte membranes and their ghosts, particularly, their microviscosity, the amount and immersion degree of membrane proteins in lipid bilayer, polarity in depth of membrane and its viscosity carried out by the spectrofluorimetric method using the hydrophobic fluorescent probe pyrene. Findings: – The carried out investigations shown that the in vitro influence of ESF changes membrane microviscosity, the quantity of membrane peripheral proteins and their immersion degree in the lipid bilayer, if the ghosts have prepared from erythrocytes previously exposed in the field. The analysis of the same parameters for previously prepared erythrocyte ghosts exposed to the 200 kV/m ESF during an hour did not reveal any changes. Originality/value: – Data obtained and their comparison with the results of the previous works allow authors to conclude that the in vitro influence of ESF leads to the changes in the lipid-protein interactions in erythrocyte membranes.